Loving Pedagogy and Second Language Learning: The Role of Teacherly Care, Motivation, and Anxiety in EFL Classrooms - Hossein Isaee; Hamed Barjesteh; Mehdi Manoochehrzadeh (Indonesian Journal of Pedagogy and Teacher Education, 2025)
Background: Loving Pedagogy has gained increasing attention in English as a Foreign Language (EFL) education as a relational and affective orientation emphasizing teacher care, empathy, and emotional responsiveness. Grounded in Positive Psychology, this perspective highlights how emotionally supportive teaching environments are associated with learners’ motivation, self-beliefs, and language development. Aims: This study examined the relationships between perceived Loving Pedagogy and EFL learners’ language learning outcomes, focusing on the mediating roles of intrinsic motivation and self-efficacy, and the moderating role of foreign language anxiety. Methods: A quantitative, correlational design was employed with 210 Iranian undergraduate EFL learners. Participants completed validated measures of Loving Pedagogy, intrinsic motivation, self-efficacy, and foreign language anxiety. Language learning outcomes were operationalized using proficiency gain scores derived from pre-/post-administration of a standardized placement test. Data were analyzed using correlational analysis, hierarchical regression, and bootstrapped mediation and moderation procedures. Results: Perceived Loving Pedagogy was positively associated with learners’ motivation, self-efficacy, and language gain scores, and negatively with foreign language anxiety. Mediation analyses indicated that intrinsic motivation and self-efficacy partially mediated the relationship between Loving Pedagogy and language learning outcomes. Moderation analysis showed that higher levels of anxiety weakened these positive associations. Conclusion: Findings suggest that Loving Pedagogy is meaningfully associated with EFL learners’ motivational and affective experiences, resulting in language development. The study extends relational and positive psychology perspectives in SLA by empirically modeling how teacher care is linked to learning outcomes through affective–motivational pathways, while highlighting the importance of learner anxiety in emotionally responsive classrooms.